Presentations and notes from a Roundtable on the metrics of sustainable diets and food systems: 27th November, 2012, Madrid, Spain - Bioversity International (2013)
Bioversity International held a Roundtable on the “Metrics of Sustainable Diets and Food Systems” in Madrid, Spain on 27 November 2012 for the Daniel and Nina Carasso Foundation which supports research and programs on sustainable diets. Over 30 academics, scientists, policy makers and others came together to discuss sustainable diets and what is needed to measure, promote and evaluate sustainable diets in different contexts. In addition to the notes from the Roundtable, there are three key note presentations presented during the Roundtable: “Health and Nutrition Implications of Econutrition: Why Sustainable Diets are Important” by Professor Richard J. Deckelbaum, Institute of Human Nutrition, Columbia University, New York, USA“Sustainable diets and policy: Why is it important?” by Professor Jennie Macdiarmid, Rowett Institute of Nutrition and Health, University of Aberdeen, UK“Sustainable Diets: Time to pilot some metrics” by Professor Lawrence Haddad, Institute of Development Studies, University of Sussex, UK